2022
DOI: 10.1007/s00453-022-00946-8
|View full text |Cite
|
Sign up to set email alerts
|

New FPT Algorithms for Finding the Temporal Hybridization Number for Sets of Phylogenetic Trees

Abstract: We study the problem of finding a temporal hybridization network containing at most k reticulations, for an input consisting of a set of phylogenetic trees. First, we introduce an FPT algorithm for the problem on an arbitrary set of m binary trees with n leaves each with a running time of $$O(5^k\cdot n\cdot m)$$ O ( 5 k · n · … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Can tree-child hybridization networks be computed faster than in O((ck) k • poly(n, t)) time, ideally in O(c k • poly(n, t)) time? For temporal networks, a recent result [8] shows that this is indeed the case. An interesting open question is whether the techniques used in that algorithm can also be used to obtain faster algorithms for computing general tree-child networks.…”
Section: Hybridization Versus Tree-child Hybridizationmentioning
confidence: 87%
See 1 more Smart Citation
“…Can tree-child hybridization networks be computed faster than in O((ck) k • poly(n, t)) time, ideally in O(c k • poly(n, t)) time? For temporal networks, a recent result [8] shows that this is indeed the case. An interesting open question is whether the techniques used in that algorithm can also be used to obtain faster algorithms for computing general tree-child networks.…”
Section: Hybridization Versus Tree-child Hybridizationmentioning
confidence: 87%
“…Indeed, in experiments on synthetic inputs, the running time grows roughly linearly in the number of trees and taxa. On the other hand, the running time still has a large exponential dependency on the number of reticulation events k. Nevertheless, as long as k is small (at most [7][8][9][10][11][12], our algorithm can solve inputs with up to 100 input trees and 200 taxa. In our experiments on real-world data, we observed that these data sets have substantially more structure than random synthetic data sets, which makes cluster reduction and redundant branch elimination more effective and allowed our algorithm to solve inputs with up to 8 trees and 50 reticulations.…”
Section: Introductionmentioning
confidence: 99%